A method for activating argillaceous sandstone uranium ore by utilizing external field coupling fenton oxidation
By combining ultrasound, microwave, or shear force field with Fenton oxidation technology, the exfoliation of clay minerals in argillaceous sandstone uranium ore is promoted, solving the problem of low uranium extraction efficiency in argillaceous sandstone uranium ore and achieving efficient, economical, and environmentally friendly uranium leaching.
Patent Information
- Application Number
- CN202510157809.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2045-02-13
AI Technical Summary
Uranium extraction from argillaceous sandstone uranium deposits is difficult, traditional leaching techniques are inefficient, Fenton oxidation reaction has limited active sites and mass transfer is restricted, making it difficult to achieve efficient leaching.
By employing the synergistic effect of ultrasound, microwave, or shear force field with Fenton oxidation technology, the exfoliation of clay minerals in argillaceous sandstone uranium deposits is promoted, the dispersion of associated pyrite and reactive sites are improved, and mass transfer efficiency and reaction rate are enhanced.
It significantly improves uranium leaching efficiency, shortens reaction time, reduces reagent dosage, and provides an efficient, economical, and environmentally friendly leaching solution.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of uranium ore resource development, and relates to a method for activating argillaceous sandstone uranium ore by using external field coupled Fenton oxidation. BACKGROUND
[0002] Argillaceous sandstone uranium ore is a special type of uranium ore containing rich mineral components. Uranium elements coexist with argillaceous minerals and pyrite, showing complex mineral distribution and occurrence state. The composite structure and close adhesion between these minerals significantly increase the difficulty of extracting uranium elements. Meanwhile, due to the relatively dense physical structure of argillaceous sandstone uranium ore, the mass transfer in the leaching process is limited, resulting in low extraction efficiency of traditional leaching technology in argillaceous sandstone uranium ore.
[0003] Due to the associated pyrite in argillaceous sandstone uranium ore, the activation of H2O2 can generate hydroxyl radicals in situ, so the Fenton oxidation technology becomes a potential choice for argillaceous sandstone uranium ore leaching. However, due to the physical characteristics and uranium occurrence mode of argillaceous sandstone uranium ore, the active sites of Fenton oxidation reaction are limited, and the leaching rate and efficiency are difficult to achieve ideal results. In addition, the peeling of argillaceous minerals and the improvement of the uniformity of associated pyrite loading are the key to improving the leaching efficiency of uranium ore, but it is difficult to effectively achieve in the existing technology.
[0004] Therefore, developing a technology that can efficiently utilize Fenton oxidation reaction and break through the mass transfer bottleneck of argillaceous sandstone uranium ore is of great significance for the extraction of uranium ore. SUMMARY
[0005] Therefore, in order to solve the above technical problems, the purpose of the present application is to provide a method for activating argillaceous sandstone uranium ore by using external field coupled Fenton oxidation, which belongs to the technical field of uranium ore resource development. The method comprises the following steps: first, adding H2O2 solution to the argillaceous sandstone uranium ore slurry and mixing uniformly, then transferring the slurry to an external field generator, utilizing the synergistic effect between ultrasonic, microwave or shear force and Fenton oxidation to oxidize U(IV) in the argillaceous sandstone uranium ore to U(Ⅵ), and then filtering the suspension to obtain high-concentration uranium leaching solution. The method for activating argillaceous sandstone uranium ore by using external field coupled Fenton oxidation provided by the present application promotes the peeling of clay minerals by external field effect, improves the dispersity of associated pyrite on the surface of clay, provides more active sites for Fenton activation reaction, and effectively accelerates the Fenton oxidation reaction. Therefore, the leaching efficiency of uranium is improved. This method significantly improves the current situation of uranium leaching difficulty in argillaceous sandstone uranium ore, obtains lower uranium content in the leaching residue, and requires shorter activation time. It is easy to be applied on a large scale.
[0006] This method overcomes the problems of mass transfer difficulty and low reaction efficiency of associated pyrite in argillaceous sandstone uranium ore. Specifically, the external field auxiliary effect plays two key roles in the leaching process of argillaceous sandstone uranium ore:
[0007] On the one hand, the ultrasonic, microwave or shear force significantly improves the mass transfer efficiency between argillaceous sandstone uranium and solvent, so that the reaction of hydrogen peroxide and pyrite is more sufficient, and the Fenton oxidation reaction is effectively accelerated. In addition, the mechanical force of ultrasonic, microwave, shear force makes the associated pyrite in argillaceous sandstone uranium and hydrogen peroxide form higher contact efficiency, thereby improving the leaching rate of uranium ore.
[0008] On the other hand, the ultrasonic, microwave or shear force affects the structure of argillaceous minerals, which causes the exfoliation phenomenon under the action of external field, which helps the loading of clay minerals on associated pyrite. The surface area of the exfoliated clay minerals increases, providing active sites for loading, which helps the continuous Fenton oxidation reaction, and provides a strong guarantee for the efficient leaching of uranium.
[0009] The present application overcomes the multiple obstacles in the leaching process of argillaceous sandstone uranium by combining external field with Fenton oxidation technology, not only improves the reaction efficiency, but also significantly enhances the extraction efficiency of uranium, and provides an innovative technical path for efficient treatment of argillaceous sandstone uranium.
[0010] In order to achieve the above purpose, the technical scheme adopted is as follows:
[0011] A method for activating argillaceous sandstone uranium by coupling Fenton oxidation with external field, comprising:
[0012] Under the assistance of external field, the hydrogen peroxide solution and the uranium ore slurry are uniformly mixed and oxidized, and after the reaction is completed, the leaching solution and the leaching residue are obtained by filtration.
[0013] The existing method for leaching argillaceous sandstone uranium mainly relies on acid or alkaline leaching agent, but due to the strong combination of uranium and clay minerals, the effect of these methods is severely limited. Clay minerals not only form a barrier to hinder the penetration of oxidizing agent, but also adsorb leaching agent and metal ions, resulting in reduced reaction efficiency. At the same time, the swelling property of clay minerals will cause the slurry to be thick and difficult to mass transfer, further affecting the extraction of uranium. In view of this, the present application proposes a new way to activate uranium in argillaceous sandstone uranium, which comprises: mixing H2O2 solution and argillaceous sandstone uranium ore slurry under the assistance of external field, and using the synergistic effect between ultrasonic, microwave, shear field and Fenton oxidation technology to improve the dispersibility of pyrite and the concentration of hydroxyl radicals.
[0014] Further, the original preparation concentration of the H2O2 solution is 0.2-2 mol / L; the pH value of the mixture is 2-7.
[0015] Further, the original preparation concentration of the H2O2 solution is 0.5-1 mol / L; the uranium ore includes argillaceous sandstone uranium.
[0016] Further, the solid content of the uranium ore slurry is 1% to 50%; and the rotation speed of the stirring is 300 to 700 rpm.
[0017] Further, the solid content of the uranium ore slurry is 5% to 10%; the concentration of the H2O2 in the uranium ore slurry is 0.1 to 1.0 mmol / L; and the external field assistance is at least one of ultrasonic field, microwave field and shear field.
[0018] Further, the concentration of the H2O2 in the uranium ore slurry is 0.3 to 0.8 mmol / L; and the activation reaction time is 30 to 60 min.
[0019] Further, the frequency of the ultrasonic wave is 30 to 60 KHZ.
[0020] Further, the microwave power is 300 to 500 W.
[0021] Further, the rotation speed of the homogenizer is 8000 to 30000 rpm; and further, the application of any one of the above activation methods to uranium leaching and uranium extraction.
[0022] Beneficial effects:
[0023] The beneficial effects of the present application are embodied in:
[0024] The present application is aimed at the characteristics of difficult leaching of argillaceous sandstone uranium ore, and overcomes multiple technical bottlenecks by coupling Fenton oxidation technology with ultrasonic, microwave or shear field, thereby bringing significant beneficial effects. Argillaceous sandstone uranium ore has a complex mineral structure, and uranium elements are usually wrapped by dense argillaceous minerals and associated pyrite, and are dispersed and difficult to leach, which makes it difficult for traditional methods to achieve ideal results in terms of mass transfer efficiency and reaction rate. Due to the close composite structure between minerals, the active sites of Fenton oxidation reaction are greatly limited in traditional processes and are difficult to utilize efficiently. The present application uses mechanical force generated by ultrasonic, microwave or shear field to loosen the mineral structure, thereby improving the contact and reaction efficiency of hydrogen peroxide and pyrite and greatly improving the mass transfer efficiency. More importantly, ultrasonic, microwave and shear action also promote the delamination effect of argillaceous minerals, significantly increasing the uniform loading of associated pyrite on the clay surface and providing more active sites for Fenton oxidation. The external field assistance and Fenton oxidation work synergistically. In this way, the leaching rate of uranium elements is significantly accelerated, and the technical problem of difficult leaching of argillaceous sandstone uranium ore is overcome.
[0025] Compared with the traditional method, the application not only makes a breakthrough in improving the uranium extraction efficiency, but also realizes cost control and environmental protection benefits by shortening the reaction time and reducing the reagent dosage, finally provides a new type of leaching scheme with high efficiency, economy and environmental protection, and completely solves the key difficulties in the leaching process of argillaceous sandstone uranium ore. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application is further described in detail below in combination with examples. It should be understood that the specific examples described herein are only used to explain the present application and not to limit the present application. If the specific conditions are not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0027] Example 1:
[0028] An external field coupling Fenton oxidation method for activating argillaceous sandstone uranium ore, comprising the following steps:
[0029] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (the uranium grade is 0.035%), the particles are fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0030] 50 g of argillaceous sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 400 rpm for 10 min to obtain a homogeneous suspension. Then 0.5 mL of H2O2 solution with a concentration of 1 mol / L is added to the above suspension, and stirred for 10 min. The suspension is transferred to an ultrasonic generator, the frequency of the ultrasonic wave is 60KHZ, and the activation time of the system is 30 min. Then the leaching system is filtered, the leaching residue is digested by digestion method, and then the content of uranium element in the digestion solution is detected by ICP-OES, and the calculation result shows that the content in the leaching residue is 0.005%.
[0031] Example 2:
[0032] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (the uranium grade is 0.035%), the particles are fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0033] 50 g of argillaceous sandstone uranium ore powder was added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. Then 0.7 mL of H2O2 solution with a concentration of 1.2 mol / L was added to the above suspension, and stirred for 10 min. The suspension was transferred to a microwave generator, and microwave power was 500 W. The microwave reaction was continued for 20 min under stirring, and then the leaching system was filtered. The leaching residue was digested by digestion method, and then the content of uranium element in the digestion solution was detected by ICP-OES, and the calculation result showed that the content in the leaching residue was 0.003%.
[0034] Example 3:
[0035] The test ore was taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (the uranium grade was 0.035%), and the particles were fine, associated with a large amount of illite, kaolinite, calcite and potassium feldspar.
[0036] 50 g of argillaceous sandstone uranium ore powder was added to 1000 mL of aqueous solution, and stirred at a stirring speed of 500 rpm for 10 min to obtain a homogeneous suspension. Then 1.0 mL of H2O2 solution with a concentration of 1.3 mol / L was added to the above suspension, and stirred for 10 min. The suspension was transferred to a homogenizer, and the rotation speed was 15000 rpm. The reaction was continued for 40 min under stirring, and then the leaching system was filtered. The leaching residue was digested by digestion method, and then the content of uranium element in the digestion solution was detected by ICP-OES, and the calculation result showed that the content in the leaching residue was 0.002%.
[0037] The test ore was taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (the uranium grade was 0.035%), and the particles were fine, associated with a large amount of illite, kaolinite, calcite and potassium feldspar.
[0038] Sulfuric acid with a mass concentration of 10% was used as leaching agent, and leaching was carried out at normal temperature and pressure.
[0039] 50 g of argillaceous sandstone uranium ore powder was added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. Then 0.7 mL of H2O2 solution with a concentration of 1.2 mol / L was added to the above suspension, and stirred for 10 min. The suspension was transferred to a microwave generator, and microwave power was 500 W. The microwave reaction was continued for 20 min under stirring, and then the leaching system was filtered. The leaching residue was digested by digestion method, and then the content of uranium element in the digestion solution was detected by ICP-OES, and the calculation result showed that the content in the leaching residue was 0.003%.
[0040] Comparative Example 2:
[0041] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0042] 50 g of sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. Then 0.7 mL of H2O2 solution with a concentration of 1.2 mol / L is added to the above suspension, and stirred for 30 min. Finally, the leaching system is filtered, the leaching residue is digested by digestion method, and then the content of uranium element in the digestion solution is detected by ICP-OES, and the result shows that the content in the leaching residue is 0.012%.
[0043] Comparative Example 3:
[0044] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0045] 50 g of sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. The suspension is transferred to a microwave generator, and the microwave power is 500 W, and the stirring state is kept for 30 min of microwave reaction, then the leaching system is filtered, the leaching residue is digested by digestion method, and then the content of uranium element in the digestion solution is detected by ICP-OES, and the calculation result shows that the content in the leaching residue is 0.019%.
[0046] Comparative Example 4:
[0047] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0048] 50 g of argillaceous sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. Then 0.5 mL of H2O2 solution with a concentration of 1 mol / L is added to the above suspension, and stirred for 30 min. Then the leaching system is filtered, the leaching residue is digested by digestion method, and then the content of uranium element in the digestion solution is detected by ICP-OES, and the calculation result shows that the content in the leaching residue is 0.016%.
[0049] Comparative Example 5:
[0050] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0051] 50 g of sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. The suspension is transferred to an ultrasonic generator, the frequency of the ultrasonic wave is 60 KHZ, and the stirring state is maintained for 30 min of ultrasonic treatment. Then the leaching system is filtered, the leaching residue is digested by digestion method, and the content of uranium element in the digestion solution is detected by ICP-OES. The calculation result shows that the content in the leaching residue is 0.021%.
[0052] Comparative Example 6:
[0053] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0054] 50 g of argillaceous sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. Then 1.0 mL of H2O2 solution with a concentration of 1.3 mol / L is added to the above suspension, and stirred for 30 min. Then the leaching system is filtered, the leaching residue is digested by digestion method, and the content of uranium element in the digestion solution is detected by ICP-OES. The calculation result shows that the content in the leaching residue is 0.011%.
[0055] Comparative Example 7:
[0056] The test ore is taken from a certain argillaceous sandstone uranium deposit in Inner Mongolia (uranium grade is 0.035%), the particle is fine, and a large amount of illite, kaolinite, calcite and potassium feldspar are associated.
[0057] 50 g of argillaceous sandstone uranium ore powder is added to 1000 mL of aqueous solution, and stirred at a stirring speed of 300 rpm for 10 min to obtain a homogeneous suspension. The suspension is transferred to a homogenizer, the stirring speed is 15000 rpm, and the stirring state is maintained for 30 min of reaction. Then the leaching system is filtered, the leaching residue is digested by digestion method, and the content of uranium element in the digestion solution is detected by ICP-OES. The calculation result shows that the content in the leaching residue is 0.0026%.
[0058] The application provides a method for activating argillaceous sandstone uranium ore based on field coupling Fenton oxidation.
[0059] In summary, the application provides a method for activating argillaceous sandstone uranium ore based on field coupling Fenton oxidation, which belongs to the technical field of uranium resource development.
[0060] The above description does not limit the application in any form, although the application has been disclosed by the above examples, which are not intended to limit the application. Any person skilled in the art can make some changes or modifications to the disclosed technical content without departing from the technical solution of the application, and any simple modification, equivalent change and modification of the above examples according to the technical essence of the application still belong to the range of the technical solution of the application.
Claims
1. A method for activating uranium ore in argillaceous sandstone using external field coupling and Fenton oxidation, characterized in that, The activation method includes: Under external field assistance, H2O2 solution and uranium ore slurry are uniformly mixed and an oxidation reaction is carried out. After the reaction is completed, the leaching solution and leaching residue are obtained by filtration. The uranium ore slurry is a slurry of argillaceous sandstone uranium ore that has been crushed and screened, with a particle size of less than 0.74 micrometers, and contains kaolinite, illite, montmorillonite clay and associated pyrite. The original concentration of the H2O2 solution is 1~2 mol / L. The external field assistance is at least one of an ultrasonic field, a microwave field, and a shear force field; the ultrasonic frequency of the ultrasonic field is 20~80 kHz; the microwave power of the microwave field is 300-500W; the shear force field is provided by a homogenizer with a rotation speed of 8000-30000 rpm; the external field action promotes the exfoliation of clay minerals and improves the dispersibility of associated pyrite on the clay surface.
2. The activation method for uranium ore in argillaceous sandstone using external field coupling Fenton oxidation as described in claim 1, characterized in that, The solid content of the uranium ore slurry is 1% to 50%; the uranium ore slurry is obtained by crushing and screening the raw uranium ore of argillaceous sandstone and stirring it in an aqueous solution at a speed of 300 to 700 rpm.
3. The activation method for uranium ore in argillaceous sandstone using external field coupling Fenton oxidation as described in claim 1, characterized in that, The solid content of the uranium ore slurry is 5%~10%; the concentration of H2O2 in the uranium ore slurry is 0.1~1.0 mmol / L.
4. The activation method for uranium ore in argillaceous sandstone using external field coupling Fenton oxidation as described in claim 1, characterized in that, The concentration of H2O2 in the uranium ore slurry is 0.3~0.8 mmol / L; the activation reaction time is 30~60 min.
5. The application of the activation method as described in any one of claims 1-4 in uranium leaching for uranium extraction.
Citation Information
Patent Citations
Ultrasonic enhanced leaching method of uranium ore
CN115679135A